Nyanyian Tradisi Lisan Masyarakat Sasak dalam Kajian Metafora Kognitif - Miswaty, Titik Ceriyani; Sumadewi, Ni Ketut Putri Nila (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Folklore is a cultural product owned by every society and believed by its people to be a unique cultural heritage containing meanings that reflect the culture of that society. This research aims to discover metaphors in the Sasak oral literature 'Seruntun' and to explore the cultural relationship with the meanings contained within 'Seruntun'. The data source for this research is 30 elders from the village of Mangkung, one of the villages that still adhere to customs on the island of Lombok and still use 'Seruntun' as a lullaby for their children. The method used in this research employs a cognitive ethnographic approach involving a cultural approach in the data analysis process. Thus, the research found that there are four metaphors in 'Seruntun' and the social and cultural contexts greatly influence the elements of literature, themes, narrative structure, and language style.